Peran Pendidikan Anti-Korupsi di Lembaga Kepolisian dalam Membentuk Anggota Polri yang Bebas Korupsi - Randywinata Randywinata (Journal of Management and Creative Business, 2024)
Anti-corruption education within the police is a strategic step in forming members of the National Police who have integrity and are free from corrupt behavior. This research aims to explore the implementation of anti-corruption education in police agencies, as well as the factors that influence its effectiveness. In this context, anti-corruption education is expected to be an important tool in instilling the values ​​of integrity among members of the National Police. Through an interview method with Mr. Yudha from Ditlantas, this research found that effective anti-corruption education involves an experience-based approach and realistic training, which allows Polri members to understand the impact of acts of corruption through simulations and real case studies. This approach is in line with Kohlberg’s theory of moral development, which emphasizes the importance of active learning in the development of ethical understanding. Apart from that, the involvement of superiors and co-workers in supporting anti-corruption education has also proven to be significant, considering that the work environment has an important role in strengthening the values ​​taught. Social environmental factors, culture and organizational structure in the police also contribute to the effectiveness of anti-corruption education. If corruption is considered accepted behavior in institutions, then education alone will not be enough to change members’ behavior. This research recommends collaboration between National Police leadership, the work environment, and ongoing training programs to support anti-corruption education. With this holistic approach, it is hoped that anti-corruption education can be implemented in real terms, so that the National Police can produce members who have high integrity and reject all forms of corruption.